Detection of signatures of selective sweeps in the Blonde d'Aquitaine cattle breed. (6th May 2013) - Boitard, S.; Rocha, D.
Summary Identifying recent positive selection signatures in domesticated animals could provide information on genome response to strong directional selection from domestication and artificial selection and therefore could help in identifying mutations responsible for improved traits. We used genotyping data generated using Illumina's BovineSNP50 Genotyping BeadChips to identify selection signatures in the Blonde d'Aquitaine breed, a well‐muscled French beef breed. For this purpose, we employed a hidden Markov model‐based test, which detects selection by studying local variations in the allele frequency spectrum along the genome, within a single population. Three regions containing selective sweeps were identified. Annotation of genes located within these regions revealed interesting candidate genes. For example, myostatin (also known as GDF8), a known muscle growth factor inhibitor, is located within the selection signature region found on chromosome 2. In addition, we have identified chromosomal regions that show some evidence of selection within QTL regions for economically important traits. The results of this study could help to better understand the mechanisms related to the selection of the Blonde d'Aquitaine breed.